2017
DOI: 10.1007/s10815-017-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

Is mitochondrial DNA quantitation in blastocyst trophectoderm cells predictive of developmental competence and outcome in clinical IVF?

Abstract: Behind every successful IVF embryo transfer, there is a great game of chance. Methods seeking to tilt the balance and increase the likelihood of implantation have been proposed and implemented with varying results, including embryo morphology, FISH-PGS, comprehensive chromosomal screening (CCS), morphokinetics, endometrial receptivity testing. It has been suggested that mitochondrial DNA (mtDNA) copy number could serve as a biomarker for embryo viability, but this concept was recently challenged. The world of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…Secondly, Reprogenetics group’s data showed mtDNA content lacked of predict power in 17 out of 35 clinics that demonstrated anything linking mtDNA content and implantation was not a universal biological phenomenon (16). That suggested it was not scientific for analyzing the mtDNA content in embryo which came from many IVF clinics together.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, Reprogenetics group’s data showed mtDNA content lacked of predict power in 17 out of 35 clinics that demonstrated anything linking mtDNA content and implantation was not a universal biological phenomenon (16). That suggested it was not scientific for analyzing the mtDNA content in embryo which came from many IVF clinics together.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the mtDNA content was further indicated to be negatively related to embryo viability and proposed to be used as a biomarker in the prediction of implanation outcome (4, 12, 14, 15). But these results were still under debate (1618). Victor et al reported a modified method that demonstrated mtDNA lacked of predictive value (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reproductive medicine identifying the embryo(s) with the highest implantation potential is still an unmet challenge, and it is a fundamental step toward single embryo transfer. During the years, several approaches have been proposed for embryo viability evaluation including embryo morphology, study of metabolic activity, extended culture, and both invasive and non-invasive preimplantation genetic testing [1,2,3,4]. Various embryological parameters have some predictive value for implantation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing a comprehensive roadmap of all cellular bioenergetics during developmental stages would offer a fundamental metabolic guide in the energetic requirements of somatic and germ-line cells, which is important for reproduction and healthy development [100][101][102], but also for tissue regeneration [95].…”
Section: The Use Of Animal Models To Study the Mtdna Bottleneckmentioning
confidence: 99%